2021
DOI: 10.52850/jtpupr.v10i2.3032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vermicompost and NPK Fertilizer to Growth and Yield of Mustard Plant (Brassica Juncea L) on Tropical Peatlands

Abstract: This research aims to determine the effect of the application Vermicompost Organic Fertilizer and NPK inorganic fertilizer in different doses to see mustard plants' growth and the yield on the media of inland peat soil. The study was a completely randomized design factorial Completely Randomized Design, consisting of 2 treatment factors and three replications. The first factor is the dose of Vermicompost organic fertilizer (D), which consisting of 3 levels i,e D0 : control ; D1: 100 g/polybag; D2 : 200 g/polyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…On average, the yield per plant was 49.20 kg. These findings are in agreement with Lautt et al (2020), who also found that the highest yield on Broad Leaf Mustard was achieved by the application of Vermicompost. Ali and Kashem (2018) found that the application of Vermicompost increased the yield of cabbage.…”
Section: Effect On Yieldsupporting
confidence: 92%
“…On average, the yield per plant was 49.20 kg. These findings are in agreement with Lautt et al (2020), who also found that the highest yield on Broad Leaf Mustard was achieved by the application of Vermicompost. Ali and Kashem (2018) found that the application of Vermicompost increased the yield of cabbage.…”
Section: Effect On Yieldsupporting
confidence: 92%